Understanding the paranormal - Duvall, Ted; Duvall, Ted (Singapore : International Publishers Direct, 2003)
Examines the reasons behind man's affinity for the unexplained, and why cultures clash in their beliefs of ghosts, spirit possessions and psychics. What the believer and non-believer can agree on is that things considered paranormal exist outside the boundary of modern science, eluding the human grasp
Executive producer, Jonathan Ward ; Executive editor, Waltor Lonkite ; editor, Paige Smith Lee
Narrator: Tracy Sallous
VCD format
Keywords: Physical research; Parapsychology